The Role of Tourism Village in Strengthening Poterry SMEs in Kasongan Tourism Village, Bantul District, Yogyakarta - Roels, Ni Made Sri Puspa Dewi; Utami, Nisa Rahmaniyah; Vania, Fidelia Brenda Pingkan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
This research was conducted to examine the role of tourism villages in strengthening pottery SMEs in Kasongan Tourism Village. Pottery products are the superior product of this village tourist attraction. The existence of pottery products cannot be separated from the role of the tourist village as a bridge to attract tourists. Data collection methods used are observation, interviews and literature study. Interviews were conducted with 20 people that are Kasongan Tourism Village managers and SMEs actors. Determination of informants using the Non-Probability Sampling technique, namely Purposive Sampling. Methods of data analysis using qualitative data analysis method. The results of the study are the role of tourism villages in strengthening SMEs which consists of making tour packages, destination branding, and partnerships. There are two tour packages, namely seeing the process of making pottery and being directly involved in making pottery. The destination branding is Kasongan Tourism Village as a pottery educational tour. Partnerships are carried out, namely working with vendors and joining cooperatives.